In vitro and in vivo metabolic stability of various fragrance materials and insect repellent in rainbow trout (Oncorhynchus mykiss). Issue 6 (11th January 2020) - Weeks, John; Guiney, Patrick; Johanning, Karla
Abstract: Commercial fragrances consist of several thousand natural and synthetic substances formulated in complex combinations. These ingredients are frequently blended at very low concentrations but they are typically lipophilic and a few of them (e.g., synthetic musks) have been detected in aquatic systems, albeit at low concentrations. Few fragrances have guideline in vivo data on bioaccumulation, so in silico modeling has been widely used to estimate bioconcentration factors (BCFs). This study used in vitro metabolism assays with trout S9 cell fractions and cryopreserved hepatocytes to improve estimates of fish BCFs and to test published methods for extrapolating in vitro metabolic rate data to whole fish and corresponding BCFs. These estimates for several chemicals were compared with new in vivo bioconcentration measurements and previously published data on fragrances and the insect repellent, DEET. In total, 17 (20 including isomers) fragrance chemicals (abalyn, amberwood, amboryl acetate, bisabolene, cedroxide, coniferan, elemol, givescone, maritima, precyclemone B, polysantol, sandela, sanjinol, santalex, timberol and vernaldehyde) and DEET were metabolized at various rates. Only three materials tested did not appear to undergo enzymatic degradation (caryophyllene oxide, galaxolide and ketone patchouli). Even relatively slow rates of metabolism had a large influence on bioconcentration estimates. This work adds valuable information to the evolving body of work supporting the use of in vitro determinations of hepatic clearance to improve modeled predictions of bioaccumulation. It can also be used directly to help prioritize testing of potential bioaccumulative chemicals or serve as a more economical method for screening these chemicals. Abstract : In vitro metabolism assays for fragrance chemicals and DEET were done using trout S9 cell fractions and hepatocytes to improve estimates of fish bioconcentration factors (BCFs) and to test published methods for extrapolating rate data to whole fish. The estimates for several chemicals were compared with new in vivo BCF measurements and previously published data. Only three of the 21 materials tested did not appear to undergo enzymatic degradation. Even relatively slow rates of metabolism had a large influence on bioaccumulation.